Strategies to Build Authorship Competence Among PhD Students. (March 2017) - Conn, Vicki S.; Jefferson, Urmeka; Cohen, Marlene Z.; Anderson, Cindy M.; Killion, Cheryl M.; Fahrenwald, Nancy L.; Benefield, Lazelle E.; Titler, Marita; Topp, Robert; Smith, Carol E.; Loya, Julio
Publication in refereed journals is an important responsibility of PhD-prepared nurses. Specialized writing skills are crucial for effective professional publication. The capacity to develop and publish articles is best learned during doctoral education. This Western Journal of Nursing Research Editorial Board Special Article addresses multi-dimensional strategies to develop authorship competence among doctoral students. The article outlines structured PhD program experiences to provide the context for students to develop authorship capacity. The authors identify multi-faceted faculty endeavors and student activities that are essential to foster authorship competence. Students who embrace opportunities to acquire authorship qualifications will be well prepared for their post-graduation role as stewards of the nursing discipline.